Penggunaan Model Pembelajaran Jigsaw untuk Meningkatkan Hasil Belajar Matematika - Sunarti, Sri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of this study was to improve student learning outcomes in learning mathematics through the Jigsaw learning model. This research method is classroom action research using a cycle model. Each cycle consists of 4 stages, namely: planning, implementation, observation, and reflection. This research was conducted in 2 cycles which were divided into 4 meetings. At the end of each cycle,  evaluation will be carried out to determine the level of achievement and completeness of students in learning. In the pre-cycle activities, the number of students whose score is 70 (KKM) is only 30% then in the first cycle it increases to 70% and in the second cycle the student learning completeness increased to 90%. Based on these results, it can be concluded that the use of the Jigsaw Learning Model can improve mathematics learning outcomes in fifth grade students of SDN 2 Randusari.